(untitled) (Journal of Student Affairs in Africa, 2021)
The widening of access into higher education institutions in South Africa has rapidly transformed the student population to become more diverse. Students vary in age, race, culture, backgrounds, educational experiences, academic potential and university expectations. Widening university access with the commensurate need for success requires intervention mechanisms to ensure university management addresses student challenges, especially at first-year undergraduate level. Access and success cannot be achieved without understanding students’ university expectations and experiences, as these are critical factors that are integrated with retention and success. This paper examines the gap between students’ expectation and experience and argues that the intensity of such a gap can negatively impact the goal of achieving access and success amongst students from diverse backgrounds. The study utilised a pre- and post-survey to collect quantitative data from 95 first-year teacher education students at a university of technology in South Africa. The results indicate that there is a significant gap between students’ expectations and their actual university experience with regard to the following indicators: social engagement, academic engagement and seeking academic support. It is posited that such a mismatch between students’ university expectations and experience can result in students feeling disconnected to the institution, which could lead to academic failure and high drop-out rates. This study recommends that an intentionally planned first-year experience programme is required to entrench a more inclusive and sustainable first-year experience for ‘all students’ which could close the gap between students’ expectation and experience and access and success.